Perception of the usability and implementation of a metacognitive mnemonic to check cognitive errors in clinical setting - Chew, Keng Sheng; Van Merrienboer, Jeroen J. G; Durning, Steven J. (BMC Medical Education, 2019)
Establishing a diagnosis is a complex, iterative process involving patient data gathering, integration and interpretation. Premature closure is a fallacious cognitive tendency of closing the diagnostic process before sufficient data have been gathered. A proposed strategy to minimize premature closure is the use of a checklist to trigger metacognition (the process of monitoring one’s own thinking). A number of studies have suggested the effectiveness of this strategy in classroom settings. This qualitative study examined the perception of usability of a metacognitive mnemonic checklist called TWED checklist (where the letter “T = Threat”, “W = What if I am wrong? What else?”, “E = Evidence” and “D = Dispositional influence”) in a real clinical setting.